2013
DOI: 10.1248/cpb.c12-01058
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint Analysis and Simultaneous Determination of Phenolic Compounds in Extracts of Curculiginis Rhizoma by HPLC-Diode Array Detector

Abstract: Curculiginis Rhizoma (Curculigo orchioides Gaertn.) is a well-known Chinese herbal medicine, as well as an important Rasayana drug in India. Current criteria of quality control on this herb are to quantitatively analyze single compound curculigoside, which fail to comprehensively evaluate quality of this herb. In this paper, a simple and reliable HPLC coupled with diode array detector (DAD) method was developed to evaluate the quality of Curculiginis Rhizoma through establishing chromatographic fingerprint and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
(18 reference statements)
2
8
0
Order By: Relevance
“…The obtained fingerprints, and relative phytocomplexes, were useful for authentication and quality control purposes, as shown in other studies [ 40 , 41 ]. Most of the research pointed out that the identified antioxidant compounds (polyphenols and vitamins) contribute significantly to the total phytocomplex of herbal preparations [ 31 , 42 ]: the present study confirmed these results, adding as well as the terpenic and organic compounds also significantly contributed to the bud-preparation phytocomplex, as anti-inflammatory and volatile constituents in herbal preparations.…”
Section: Resultssupporting
confidence: 63%
“…The obtained fingerprints, and relative phytocomplexes, were useful for authentication and quality control purposes, as shown in other studies [ 40 , 41 ]. Most of the research pointed out that the identified antioxidant compounds (polyphenols and vitamins) contribute significantly to the total phytocomplex of herbal preparations [ 31 , 42 ]: the present study confirmed these results, adding as well as the terpenic and organic compounds also significantly contributed to the bud-preparation phytocomplex, as anti-inflammatory and volatile constituents in herbal preparations.…”
Section: Resultssupporting
confidence: 63%
“…Fast screening techniques and simple sample preparation are growing priorities intended to make methods more convenient and cost-effective: chromatographic fingerprint, a more significant formulation for controlling the quality of herbal medicines and their products, has been accepted by many countries and organizations. To provide a fingerprint, the entire chromatogram may be used as a chemical profile, or a chromatographic discriminating region or a selection of significant chemical markers: in this study, all the chromatographic pattern was used for fingerprint evaluation, according to other similar studies (Bian et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Curculiginis Rhizoma, the dry rhizome of C. orchioides, is a well-known Chinese herbal medicinal product and also an important Ayurvedic product used for the treatment of pain, inflammation, immune and hepatic disorders, and as an aphrodisiac [79]. Curculigoside, a phenolic glycoside, is considered to be the major contributor to the medicinal properties of this herbal product.…”
Section: Curculiginis Rhizoma (Curculigo Orchioides)mentioning
confidence: 99%